Hepatitis A outbreak in HIV-infected patients in Southeastern France: questions and responses?. (17th April 2020) - Martin, A.; Meddeb, L.; Lagier, J. C.; Colson, P.; Menard, A.
Abstract: During the 2017 European hepatitis A (HA) outbreak we assessed HA incidence in our cohort of 2300 HIV-infected patients, implemented preventive measures and evaluated practices and knowledge on sexually transmitted diseases (STD). HA incidence was assessed between 1 January 2017 and 31 December 2017 and included all symptomatic patients with virologically confirmed HA. Preventive measures consisted in identifying at risk and not immunised patients to propose them a free HAV vaccination, and an anonymous survey related to transmission routes of STD and to sexual behaviours. Twenty HA were diagnosed. All were homosexual men recently diagnosed with HIV and another STD. None were vaccinated against hepatitis A virus (HAV). Hospitalisation was required for 52%. We identified 250 patients at risk to acquire HAV and invited them to a free immunisation program. A total of 110 (44%) were vaccinated, of whom 74 responded to our survey. A majority of them (84%) reported recent active anal and oral sexuality with multiple (52%) male partners (81%), and ChemSex consumption (14%). Internet was the meeting link for 58%. Another STD history was found in 69%. One third of these individuals had no idea about STD transmission modes. This HA outbreak pointed the insufficient vaccine coverage against HAV and knowledge on STD, which may be improved by Internet.